The Role of Multimodal Approach in Enhancing Reading Comprehension Skills in Junior High School Students - Sulthan Fari Farras Fathin; Mutiarani Mutiarani (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study investigates the effectiveness of a multimodal approach in improving students’ English reading comprehension at SMPN 10 South Tangerang during the 2025/2026 academic year. Involving 42 eighth-grade students, the research aimed to determine whether integrating various modes of learning—such as text, images, audio, and video—could enhance reading comprehension more effectively than traditional text-based instruction. A pre-experimental one-group pre-test and post-test design was used to measure students’ progress before and after the implementation of multimodal learning. Data were analyzed using a paired sample t-test to identify significant differences between the two tests. The results indicated a notable improvement, with the mean score increasing from 70.48 on the pre-test to 79.76 on the post-test, representing a gain of 9.28 points. The significance value (Sig. 2-tailed = 0.000) confirmed that the improvement was statistically meaningful. These findings demonstrate that multimodal instruction enhances comprehension by presenting information through multiple sensory channels, supporting diverse learning preferences, and creating a more engaging and interactive learning environment. The study concludes that the multimodal approach is an effective method for teaching reading comprehension in junior high school and recommends broader application in English classrooms to strengthen students’ motivation, understanding, and overall learning outcomes.